Assessing the Perceptions and Practice of Self-Medication among Bangladeshi Undergraduate Pharmacy Students - Md. Omar Reza Seam; Rita Bhatta; Bijoy Laxmi Saha; Abhijit Das; Md. Monir Hossain; S. M. Naim Uddin; Palash Karmakar; M. Shahabuddin Kabir Choudhuri; Mohammad Mafruhi Sattar (MDPI AG, 2018)
Objectives: To evaluate the perceptions and extent of practicing self-medication among undergraduate pharmacy students. Methods: This cross-sectional, questionnaire-based study was conducted over a six month period (January to June 2016) among undergraduate pharmacy students in five reputable public universities of Bangladesh. It involved face-to-face interviews regarding self-medication of 250 respondents selected by simple random sampling. Results: Self-medication was reported by 88.0% of students. Antipyretics (58.40%) were mostly preferred for the treatment of fever and headaches. The major cause for self-medication was minor illness (59.60%, p = 0.73) while previous prescriptions were the main source of knowledge as well as the major factor (52.80%, p = 0.94) dominating the self-medication practice. The results also demonstrated 88.80% of students had previous knowledge on self-medication and 83.60% of students always checked the information on the label; mainly the expiry date before use (85.60%). A significant (p < 0.05) portion of the students (51% male and 43% female) perceived it was an acceptable practice as they considered self-medication to be a segment of self-care. Furthermore, students demonstrated differences in their response level towards the adverse effect of drugs, the health hazard by a higher dose of drug, a physician's help in case of side effects, taking medicine without proper knowledge, and stopping selling medicine without prescription. Conclusions: Self-medication was commonly used among pharmacy students primarily for minor illnesses using over-the-counter medications. Although it is an inevitable practice for them it should be considered an important public health problem as this practice may increase the misuse or irrational use of medicines.